The effects of personality traits and perceived organisational injustice on deviant workplace behaviours: a review of the literature - Muhammad Amin Bujang,; Mohammad Rahim Kamaluddin,; Jamiah Manap,; Mohd. Nasir Selamat, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Deviant behaviour in the workplace has negative repercussions, not only for the financial and material losses that are experienced by the organisation but also for the personal welfare of the employees who operate inside the organisation. In this article, the author discusses the ways in which personality traits and the perception of organisational injustice might contribute to deviant behaviours in the workplace. The purpose of this article is to provide an understanding and justification of two exogenous variables and their relationship to deviant workplace behaviours. This will be accomplished through the utilisation of a narrative literature review that has been carried out based on secondary data obtained through electronic databases and some references from articles and journals. According to the narrative literature review, more terms were used as a starting point for studies that similarly examined deviant workplace behaviour that falls into the organisational and interpersonal categories. In addition, the findings of the study demonstrated the types of personality traits and organisational injustice that were chosen together with the research tools that were utilised by the researchers to recognise and comprehend relationships and connections. The findings also indicated that previous studies have utilised third variables as moderators or mediators in examining the association between personality traits, perceived organisational injustice and deviant behaviour in the workplace. This study further enhances the current body of literature that is crucial for comprehending the impact of personality traits and perceived organisational injustice on deviant workplace behaviours.